Enhancing health outcomes for Māori elders through an intergenerational cultural exchange and physical activity programme: a cross-sectional baseline study - Oetzel, John G.; Zhang, Yingsha; Nock, Sophie; Meha, Pare; Huriwaka, Huia; Vercoe, Maramena; Tahu, Tania; Urlich, Joanne; Warbrick, Rachel; Brown, George; Keown, Shirley; Rewi, Poia; et al. (Frontiers in Public Health, 2023)
Background. Māori kaumātua (Indigenous elders) face significant social and health inequities relative to non-Māori populations in Aotearoa New Zealand that are explained by a variety of structural determinants including colonial history and racism. This study offers baseline data for a strengths-based approach emphasising intergenerational cultural knowledge exchange and physical activity developed through a partnership with kaumātua (elders) and service providers.Methods. The study design is a cross-sectional survey of 75 kaumātua from six providers; participants completed two physical functioning tests and a survey that included variables based in a holistic model of health.Results. The findings indicate that there was good reliability and moderate scores on most variables. Specific correlates included the following: a) health-related quality of life: emotional support (β=.31), and frequent interaction with a co-participant (β=.25); b) selfrated health: frequency of moderate exercise (β=.32) and sense of purpose (β=.27); c) spirituality: sense of purpose (β=.46), not needing additional help with daily tasks (β=.28), and level of confidence with cultural practices (β=.20); d) life satisfaction: sense of purpose (β=.57), frequency of interaction with a co-participant (β=-.30), emotional support (β=.25), and quality of relationship with a co-participant (β=.16); and e) lower loneliness: emotional support (β=.27), enjoyment interacting with a co-participant (β=.25), sense of purpose (β=.24), not needing additional help with daily tasks (β=.28), and frequency of moderate exercise (β=.18).This study provides the baseline scores and correlates of important social and health outcomes for the He Huarahi Tautoko (Avenue of Support) programme, a strengthsbased approach for enhancing cultural knowledge engage and physical activity.